Viv??ncias e significados de cuidadores homens de parentes com Alzheimer, atrav??s de sua narrativa - Moreira, Marcos Lameira (2014)
With the advance of times, our efforts towards a greater longevity were rewarded with a moment where our lifespan is prolonged more and more, bringing questions and reflections about the quality of life, required by this new population profile. However this demographic change is not presented to us without its demands, which can be increasingly seen in the changes that our society has undergone, because with aging we also diseases regarding that period and in them, we see the increasing emphasis on the caregiver. Caregivers who often end up unprepared for an erroneously associating the act of aging to diseases that limit the daily life of the elderly, affecting their quality of life as well as that of those around them. This paper aims to understand the men who are informal family caregivers to elder patients with Alzheimer's disease, through their narratives. The current study was done according to four stages: The first sought to understand the topic through a literature review on the subject, its concepts and developments; In the second step, the method used was qualitative, descriptive and exploratory, to identify the stories and issues presented by these caregivers; the third step, in turn, sought to conduct a field study in which semi-structured interviews were conducted and the Zarit scale was used to measure the degree of overloading within these caregivers; the final step dealt with the analysis and discussion of the collected data. We analyzed the data and with the results we tried to correlate the reports of the interviewed to the observed data. It is believed that the results obtained may serve as a contribution to both the academic field as well as for areas that provide assistance to informal caregivers, like these who participated in this research.